Depth profiles and free volume in aircraft primer films. (May 2015) - Van Horn, J D; Chen, H; Jean, Y C; Zhang, W; Jaworowski, M R
Abstract: Positron annihilation lifetime spectroscopy (PALS) and associated techniques provide non-destructive methods to study the free volume inside polymeric materials, and to study material characteristics over a depth profile. Cast free films of organic- or aqueous-based, non-chromated aerospace primers, when cured for about one week, had very different water vapour transport (through-plane) behaviour. In addition, both types of primer films showed strong anisotropic behaviour in in-plane versus through-plane water vapour transport rates. We report the differences between the organic- and aqueous-based aircraft primer films samples and their surface depth profiles. In bulk PALS measurements, an aged, organic-based film exhibited typical lifetimes and intensities for a particulate-containing polymer film on both faces. In contrast, aqueous-based films exhibited face oriented-dependent differences. In all aqueous- based samples, the I3 value of the back of the sample was smaller. The primer film samples were also evaluated with mono-energetic positron beam techniques to generate depth profile information. The heterogeneity in the samples was verified by Doppler broadening of energy spectroscopy (DBES). A model for the differences in the faces of the films, and their layered structure is discussed.